Plant and livestock waste compost compared with inorganic fertilizer: nutrient contribution to soil. (TERRA LATINOAMERICANA, 2017)
The use of livestock and plant wastes, as sources of nutrients and organic material to the soil, is a viable alternative to chemical fertilizers, which eventually cause serious risks to agroecosystems. The present study was conducted in 2013 in a greenhouse at FACIATEC-UACH, Chihuahua, México. Four composts made with (a) cow manure, (b) hen manure, (c) sawdust and (d) maize stover were evaluated for their contribution of the soil macronutrients NO3-, P=, K+, Ca++, Mg++ and Na+ and compared with urea as a synthetic fertilizer and a control without fertilizer. The experiment was based on a completely randomized design; statistical analysis included an analysis of variance using the statistical package SAS (Statistical Analysis System) version 9.3.1 and comparison of means with the Tukey procedure (a = 0.05). Results suggest that f ive of the compost treatments increased the concentration of NO3-. Hen manure signif icantly outperformed cow manure in providing NO3- and P=. Likewise, the sawdust-based compost signif icantly affected the content of NO3-, outperforming the treatment based on maize stover. The concentration of Ca++ and Mg++ in soils resulting from the applied composts was lower than in the treatment with inorganic fertilizer, but that of Na+ was statistically higher than in the inorganic fertilizer treatment. This evidence suggests that the use of organic fertilizers, of either animal or plant origin, is a benef icial source of soil nutrients with high potential in sustainable agriculture.
Keywords: Macronutrients; organic matter; soil fertility.